(untitled) (Research, Society and Development, 2021)
This preclinical study aimed to evaluate the tissue repair process of burns treated with human amniotic membrane (hAM) patches in rats. Twenty-four rats were subjected to superficial burns of partial thickness, and randomly allocated into two groups: Control and Treated Group, subdivided into two experimental periods of 7th and 14th days. The lesions were evaluated by digitalized images (macroscopy) and by the analysis of histological sections stained in H&E to quantify the number of inflammatory cells and fibroblasts present in the different experimental times (histomorphometry). The histomorphometric analyses were performed blindly. Statistical analysis employed Kolmogorov-Smirnov and Mann Whitney tests, with 95% confidence interval at 5% significance level (p <0.05). Macroscopically, the lesions of Treated group presented a crust formation before Control Group, and there were no signs of infection in both groups. Microscopically, the qualitative analysis showed a faster evolution in the healing process of the Treated groups compared to the Control, with reduction of the inflammatory infiltrate, intense fibroblasts proliferation and better organization of the collagen fibers. The quantitative analysis showed statistically significant results regarding the reduction of inflammatory cells (p<0.0001) at 7th and 14 th day and increased proliferation of fibroblasts at 14th day (p<0.0001) in lesions treated with hAM compared to Control group. The results of this preclinical study demonstrated that the application of hAM patches reduces the inflammatory process and accelerates the onset of the proliferative phase in burn injuries.